Codependencia emocional en mujeres estudiantes de psicología de la Universidad Cooperativa de Colombia sede Villavicencio (2024)
Emotional codependence is the tendency that some people have for affective dependence with an obsessive characterization towards the other person and their love relationship, this becomes an emotional problem because all the time they feel the need to be with that person leaving aside their own interests and minimizes and denies their feelings and lacks empathy with the feelings and needs of others and not only that but also allowing some kind of violence either physical or verbal and affecting their self-esteem, in addition to this can generate conflicts at levels of their daily life and evidenced more in young people, Thus, the present study aims to identify the level of emotional codependence in women of the psychology career of the University Cooperative of Colombia, from a quantitative approach, descriptive type, cross-sectional with a sample of 142 university women in the age range of 18 to 21 years, for this the instrument of emotional codependence ICOD was applied, it is validated by (Noriega, 2013). From the results obtained in the instrument indicate that women in the faculty of psychology at the University Cooperative of Colombia in Villavicencio are in a possible emotional codependence, that is, at a high level.